katG (SER 315 THR) Gene Mutation in Isoniazid Resistant Mycobacterium Tuberculosis - Marahatta, S B; Gautam, S; Dhital, S; Pote, N; Jha, A K; Mahoto, R; Mishra, S; Poudel, B H; Ramasoota, P; Kaewkungwal, J; Singhasivanon, P (Kathmandu University Medical Journal, 2012)
Background Isoniazid (INH) together with Rifampicin (RFP) forms the cornerstone of a short chemotherapy course for tuberculosis (TB) treatment. Mutation at codon 315 of katG gene is most prevalent in isoniazid resistant Mycobacterium tuberculosis (MTB) and is high in area with high TB incidence. Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) has been found to be a reliable and effective tool for the identification of the specific gene alteration. Objective The objective of this study was to screen Ser315Thr mutation of KatG gene of INH resistant MTB strain by PCR-RFLP technique. Methods Altogether 37 INHr MTB isolates obtained from German Nepal Tuberculosis Project (GENETUP) Kathmandu Nepal was included in the study. Deoxyribonucleic Acid (DNA) extraction was performed according to protocol of SORPOCLEAN™ from the culture isolates. Amplification of the fragment with katG codon 315 was performed in a Biometra Thermocycler using primers. The amplified fragment was cleaved with MspI. The restriction fragments obtained were electrophoresed in a 2% agarose gel and were visualized using transilluminator. Results The katG Ser315Thr mutation was observed in 23 (62.2%) out of 37 INH resistant isolates. The drug susceptibility profile of INHr MTB isolates showed all isolates to be resistant to INH and RFP whereas 26 and 27 MTB isolates were resistant to Ethambutol (EMB) and Streptomycin (S) respectively. Seventeen (17) patients were harbouring katG gene mutated strain among Ethambutol and Streptomycin resistant cases. Conclusion The study identified high prevalence of Ser315Thr mutation in katG. The isolates harbouring this mutation were also simultaneously resistant to RFP. Ser315Th could be a potential genetic marker for predicting MDR-TB http://dx.doi.org/10.3126/kumj.v9i1.6256 Kathmandu Univ Med J 2011;9(1):19-23